Intercultural problems in "Anna and The King": a discourse approach - Iwik Pratiwi (Jurnal Linguistik Terapan, 2014)
The loads of value in “Anna and the King” (1999), a film based on a diary written by Margaret Landon in 1944 provides an accurate and extensive basis for exploration of interlanguage communication used in real life. It tells about the English woman who became a teacher in Siam in King Mongkut’s era and explores a continuous negotiation between cultural practices and other socio-political determinants which promote the Royal institution in the Thai everyday life. This paper is to reveal an interdiscourse communication represented in a scene taken from the film emphasizing on the situation represented in a dialogue in which members of different groups are in social interaction with each other and the interpretive processes they must bring to bear to understand each other in a highly altered hybrid and culturally mixed situation. The discussion is based on a discourse approach proposed by Ron Scollon, Suzanne Wong Scollon and Rodney H. Jones (2012) in their book: “Intercultural Communication”. The speech situation, speech events, and speech acts are outlined before discussing the grammar of context. Then the background discourse is elaborated before analyzing the occurring problems during the intercultural communication between Anna, an English woman and King Mongkut, a Siamese ruler. The discussion is mainly based on Western vs Eastern, Utilitarian vs Confucian, deductive culture vs inductive culture dichotomies. It is concluded that the miscommunication is due to different discourse system which includes ideology forms of discourse, partial socialization and different perception of face system.